Parallel processing and high performance computing with clusters and grid - Jani,N.N...[et al] (Everest Pub House, 2010)
Parallel processing and high performance computing with clusters and grid / Jani,N.N...[et al]. -- Pune: Everest Pub House, 2010 004.3 J33 No. of Copies : 1